2022
DOI: 10.4414/smw.2022.w30197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of type 2 diabetes care management in nine primary care practices before and after implementation of the Criteria of Good Disease Management of Diabetes established by the Swiss Society of Endocrinology and Diabetology 

Abstract: CONCLUSION: Overall, the implementation of the SSED criteria in the current setting led to a modest, nonsignificant improvement of the diabetes score. Only three (all single practices) out of the nine practices reached the recommended 70-point target, indicating that further strategies are needed to improve diabetes care in primary care practice.Trial registration: ClinicalTrials.gov (ID NCT04216875).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The percentage of patients with diabetes successfully controlling their blood pressure (63.3%) and LDL cholesterol (54.4%) still lags the SSED guidelines. Our results are similar to a recent analysis of nine general practices in St Gallen,22 which reported that glycemic control was a little under 60%, and blood pressure and LDL cholesterol control was only achieved in half of the patients. In contrast, an analysis of 365 patients with type 2 diabetes at two tertiary care centers in the cities of Bern and St Gallen reported that blood pressure <140/90 mm Hg was achieved by 92% of patients with diabetes 23.…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of patients with diabetes successfully controlling their blood pressure (63.3%) and LDL cholesterol (54.4%) still lags the SSED guidelines. Our results are similar to a recent analysis of nine general practices in St Gallen,22 which reported that glycemic control was a little under 60%, and blood pressure and LDL cholesterol control was only achieved in half of the patients. In contrast, an analysis of 365 patients with type 2 diabetes at two tertiary care centers in the cities of Bern and St Gallen reported that blood pressure <140/90 mm Hg was achieved by 92% of patients with diabetes 23.…”
Section: Discussionsupporting
confidence: 91%
“…Considering that non-adherence to diabetes medical standards (<2 × HbA1c, Lipid profile at target, nephropathy status and ophthalmologist visit per year) in diabetes care is associated with an increased probability of future hospitalization among patients with diabetes [26,27] (table 2). The suggested target in practice is ≥70 out of 100 points among all patients with type 2 diabetes mellitus [27].…”
Section: Adherence and Sged/ssed Scorementioning
confidence: 99%
“…Score[26,27]: suggested target: ≥70/100 points.Criteria Intervention Aim (on a yearly basis) PointsRegular visits General diabetes control <80% of patients with ≥3 visits10 Lifestyle measures BMI >25, physical exercise, and nutrition counselling <80% of patients have BMI ≤25 or if BMI >25 received counselling ≥1/year 5 Nicotin abuse: smoking cessation counselling >80% patients non-smokers or if active smokers received 15 LDL-C if <75 years of age LDL-Cholesterol measurement Annual mean: ≥63% of patients <2.6 mmol/l 10 Nephropathy screening Measurement of serum creatinine + microalbuminuria ≥80% of patients screened 10 Retinopathy screening Ophthalmological consultation ≥80% of patients screened at least every second year 10 Foot examination Pulses (Arteria dorsalis pedis, Arteria tibialis posterior), monofilament and vibration sense ≥80% of patients screened 10 BMI: Body Mass Index; DCCT: Diabetes Control and Complications Trial; HbA1c: haemoglobin A1c; LDL: low-density lipoprotein cholesterol; SGED/SSED: Swiss Society for Endocrinology and Diabetes Review article: Medical guidelines Swiss Med Wkly. 2023;153:40060…”
mentioning
confidence: 99%